Prion infectivity in variant Creutzfeldt–Jakob disease rectum. Issue 1 (8th June 2006) - Wadsworth, J D F; Joiner, S; Fox, K; Linehan, J M; Desbruslais, M; Brandner, S; Asante, E A; Collinge, J
Abstract : Background: Disease-related prion protein (PrP Sc ) is readily detectable in lymphoreticular tissues in variant Creutzfeldt–Jakob disease (vCJD), but not in other forms of human prion disease. This distinctive pathogenesis, with the unknown population prevalence of asymptomatic vCJD infection, has led to significant concerns that secondary transmission of vCJD prions will occur through a wide range of surgical procedures. To date PrP Sc :prion infectivity ratios have not been determined in vCJD, and it is unknown whether vCJD prions are similar to experimental rodent prions, where PrP Sc concentration typically reflects infectious prion titre. Aim: To investigate prion infectivity in vCJD tissue containing barely detectable levels of PrP Sc . Methods: Transgenic mice expressing only human PrP (Tg(HuPrP129M +/+ Prnp o/o )-35 and Tg(HuPrP129M +/+ Prnp o/o )-45 mice) were inoculated with brain or rectal tissue from a previously characterised patient with vCJD. These tissues contain the maximum and minimum levels of detectable PrP Sc that have been observed in vCJD. Results: Efficient transmission of prion infection was observed in transgenic mice inoculated with vCJD rectal tissue containing PrP Sc at a concentration of 10 4.7 -fold lower than that in vCJD brain. Conclusions: These data confirm the potential risks for secondary transmission of vCJD prions via gastrointestinal procedures and support the use of PrP Sc as a quantitative marker of prion infectivity in vCJD tissues.